The knowledge, attitudes and practices of hand, foot, and mouth disease prevention strategies amongst parents and educators of children under 5 years amidst COVID-19 pandemic: A cross-sectional study - Wang, Min Xian; Pang, Junxiong (Frontiers in Public Health, 2022)
Background Hand, Foot Mouth Disease (HFMD) is endemic in Singapore. Prevention efforts have been ramped up since major outbreaks in the early 2000s. This study aims to assess the current knowledge, and attitudes towards and practise (KAP) levels of HFMD prevention strategies (HFMD-PS) among parents and teachers of children under five years amidst the COVID-19 pandemic. Methods and Results A convenience sample of 240 teachers and 404 parents responded to self-administered standardised questionnaire between mid-October and December 2020. A scoring framework was used to assess responses in the “knowledge”, “attitude” and “practice” domains. Multivariable analysis adjusted for ethnicity and attitudes towards getting children to follow proper handwashing steps and regularly disinfecting children’s toys among parents; knowledge about HFMD’s infectious period and the responses to a child turning symptomatic in the childcare centre among teachers. Existing levels of knowledge and attitudes in parents and teachers were not high and only a small proportion practised high levels of prevention measures (99 parents and 28 teachers). Key facilitators for higher practise level in parents include 1) awareness of regular liquid soap’s efficacy as a disinfectant, 2) toy cleaning before and after playtime and 3) the cleaning agent used for this practice. Teachers had no significant factors associated with higher practise levels. Conclusions This study suggested potential gaps between positive knowledge and attitudes towards prevention strategies, and its actual adoption levels in homes and childcare centres during COVID-19 pandemic. These evidences suggest the importance of continuous promotion of HFMD prevention practise in homes and childcare centres, even amidst pandemics.